2016
DOI: 10.1093/geronb/gbw132
|View full text |Cite
|
Sign up to set email alerts
|

Adapting to Aging: Older People Talk About Their Use of Selection, Optimization, and Compensation to Maximize Well-being in the Context of Physical Decline

Abstract: Objectives:Selection, Optimization, and Compensation (SOC) may contribute to successful aging by helping older people maximize well-being in the context of physical decline. To explore this hypothesis, and to investigate the potential for narrative analysis to improve understanding of SOC, we analyze interviews conducted with 15 members of the 6-Day Sample, a cohort of Scots born in 1936.Method:Interviewees were chosen based on their physical function and well-being scores. Interviews were analyzed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 47 publications
(67 reference statements)
5
57
0
10
Order By: Relevance
“…Studies have shown that older adults' have a variety of strategies in place to maximise independence and well‐being in the context of physical decline (Baltes & Baltes, ; Carpentieri, Elliott, Brett, & Deary, ; Nazil, ). In terms of ageing, individuals who are able to maintain higher levels of functioning despite adversity experienced are thought to demonstrate resilience (Cosco, Howse, & Brayne, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that older adults' have a variety of strategies in place to maximise independence and well‐being in the context of physical decline (Baltes & Baltes, ; Carpentieri, Elliott, Brett, & Deary, ; Nazil, ). In terms of ageing, individuals who are able to maintain higher levels of functioning despite adversity experienced are thought to demonstrate resilience (Cosco, Howse, & Brayne, ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant outcome of stigma is that affected individuals may delay or avoid seeking help . However, the narrative used by older adults when talking about ageing has also been associated with health, life satisfaction and quality of life (Carpentieri, Elliott, Brett, & Deary, 2017). Positive attitudes towards ageing are recognised as important drivers of healthy mental and physical ageing (Bryant et al, 2012;Carpentieri et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The WEMWBS was developed for use with nationwide samples, has been used to study public religiosity, and captures multiple mental well‐being aspects such as self‐actualization, happiness, and psychological functioning (Carpentieri et al. ; Pandya ; Tennant et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…The dependent measure-mental well-being-was measured using the validated (Englishlanguage) WEMWBS (Tennant et al 2007). The WEMWBS was developed for use with nationwide samples, has been used to study public religiosity, and captures multiple mental well-being aspects such as self-actualization, happiness, and psychological functioning (Carpentieri et al 2016;Pandya 2015;Tennant et al 2007). In terms of the appropriateness of this measure for religious stress-buffering models, the WEMWBS covers many of the mental health aspects of the religious stress-buffering studies reviewed in Table 1.…”
Section: Methodsmentioning
confidence: 99%